English language arts as an emancipatory subject : international perspectives on justice and equity in the English classroom - Goodwyn, Andrew, 1954-; Durrant, Cal; Manuel, Jacqueline; George, Marshall; Sawyer, Wayne; Shoffner, Melanie (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"English Language Arts as an Emancipatory Subject explores the changing nature and history of the English Language as an emancipatory subject, as well as how its current activities and projects address and challenge inequalities. Various forms of critical literacy have established English teaching as a radical force for social justice and subversion. However, the expert contributors to this book question whether English is a force for good in its capacity to develop literate citizens, or, are there larger contemporary complications surrounding it? This book will re-examine the history of English, its present quality as a classroom subject and its future potential to re-establish itself as an agent of social equality and change. Edited by internationally leading scholars from the UK, USA and Australia with contributions from New Zealand and Canada, this work will also inspire English teachers to view their subject as one through which positive differences are imagined, and complex real-life issues are debated and challenged in the classroom. The volume is an excellent overview of research and the latest thinking about the nature of English as an emancipatory subject, its distinguished history and its potential for the future. It will be a key resource for the research and teacher-education community, English teachers, student teachers, and anyone who views English teaching as a catalyst of social change"--
Keywords: English language -- Study and teaching -- Political aspects; English language -- Study and teaching -- Social aspects; Social justice and education; Liberty; EDUCATION / Comparative; EDUCATION / Teaching Methods & Materials / Reading; EDUCATION / Educational Policy & Reform / General